Mutation analysis of exon 3 and 4 of α-synuclein gene in Parkinson’s disease patients from west Libya - Awayn, Nuri (The Libyan Journal of Science, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by losing dopaminergic neurons. The aetiology of Parkinson’s disease remains unclear. It is believed that a combination of environmental, age, and genetic factors influence disease pathogenesis. There are few point mutations which have been reported in the a-synuclein gene from PD patients from different ethnic groups (A30P, E46K, H50Q, G51D, A53T, A53E). Here, we collected blood samples from 70 PD patients and 30 healthy controls selected from the west Libyan population that have been matched for ethnic and environmental origin. Genomic DNA was extracted from these samples. Mutation analysis was performed by PCR amplification of the exon 3 and exon 4 of the a-synuclein gene from chromosomal DNA and then sequenced. However, we failed to detect any mutation in exon 3 and 4 including the previously reported mutations. These results suggest that mutation in the a-synuclein gene is an uncommon cause of PD pathogenesis. Furthermore, our data adds further support to the results obtained from worldwide mutation screening in that the a-synuclein gene is a rare cause of PD pathogenesis.